ZIF-67-based catalysts for oxygen evolution reaction. Issue 28 (7th July 2021) - Wen, Hui; Zhang, Shengqi; Yu, Tao; Yi, Ziyu; Guo, Rui
Abstract : As a new type of crystalline porous material, the imidazole zeolite framework (ZIF) has attracted widespread attention due to its ultra-high surface area, large pore volume, and unique advantage of easy functionalization. Abstract : As a new type of crystalline porous material, the imidazole zeolite framework (ZIF) has attracted widespread attention due to its ultra-high surface area, large pore volume, and unique advantage of easy functionalization. Developing different methods to control the shape and composition of ZIF is very important for its practical application as catalyst. In recent years, nano-ZIF has been considered an electrode material with excellent oxygen evolution reaction (OER) performance, which provides a new way to research electrolyzed water. This review focuses on the morphological engineering of the original ZIF-67 and its derivatives (core–shell, hollow, and array structures) through doping (cation doping, anion doping, and co-doping), derivative composition engineering (metal oxide, phosphide, sulfide, selenide, and telluride), and the corresponding single-atom catalysis. Besides, combined with DFT calculations, it emphasizes the in-depth understanding of actual active sites and provides insights into the internal mechanism of enhancing the OER and proposes the challenges and prospects of ZIF-67 based electrocatalysts. We summarize the application of ZIF-67 and its derivatives in the OER for the first time, which has significantly guided research in this field.